Leftist Catholic movements in France before the challenge on May 1968 - D.V. Shmelev (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper examines the activities and ideology of the leftist Catholic movements in the light of the events of May 1968 in France. The paper is based on the modern historiographic material with the involvement of a wide range of sources. The analysis covers the sources of political engagement of the French Catholics (features of political career, social belonging, crisis of religious practice, as well as the role of trade unions, heritage of the “Christian Leftism”), forms of organization and political socialization, models of political behavior, demands, intellectual routes, evolution of relations with church authorities and perception of renewal movements in the Church, attitude to Marxism and the challenges of the modern era. Some demarches of the leftist Catholics have been considered. Their participation in major manifestations of the late 1960s has been investigated. The reasons for involvement in the May events of 1968 have been discussed. Furthermore, the emergence, ideological origins (Christian progressism, movement for peace, and de-Stalinization), and forms of manifestation and specificity of the French ultra-leftism (gauchism) have been studied. The significance of the events of May 1968 in France for the evolution of leftist Catholics has been traced. It has been noted that the leftist Catholics in various versions actively participated in the events of May 1968, putting forward their slogans and demands, passing through political socialization and ideological baptism, but the surge of their political activity became not only one of the symptoms of the ideological crisis, but also the beginning of a decline in the popularity of Marxism in France, as well as the rise of extremely leftist groups sympathetic to Maoism, anarchism, or Trotskyism.